Philanthotoxin-343 attenuates retinal and optic nerve injury, and protects visual function in rats with N-methyl-D-aspartate-induced excitotoxicity - Fazel M.F.; Abu I.F.; Mohamad M.H.N.; Agarwal R.; Iezhitsa I.; Bakar N.S.; Juliana N.; Mellor I.R.; Franzyk H. (Public Library of Science, 2024)
Indexed by WOS/Scopus/ERA